Low-temperature plasma priming enhances nutrient removal and astaxanthin production in Haematococcus pluvialis: Transcriptomic responses during controlled aquaculture wastewater cultivation - Zuo Lin; Chen Zhu; Wang Fen; Ha Thanh Dong; Takuji W. Tsusaka; Nimish Devendra Dhuri; Jiang Yelin; Zhou Xiang; Krishna R. Salin (Bioresource Technology, 2026)

Removal of microplastics in water and wastewater: prospects toward a circular economy - Van-Hiep Hoang; Minh-Ky Nguyen; Tuan-Dung Hoang; Chitsan Lin; Minh Cuong Ha; Nguyen Thi Thanh Huyen; Adnan Hussain; X. Hoan Nguyen; Woojin Chung; D. Duc Nguyen (Clean Technologies and Environmental Policy, 2026)

Characteristics and driving factors of population age structure in China: A study based on the scale nesting theory - Kui Ying; Lin Ha; Liancheng Duan; Jinhong Ding (Journal of Geographical Sciences, 2026)

Regional assessment of heavy metal–related ecological risks in the Houjing river sediments in Taiwan: A study using indexes and extreme gradient boosting model - Hong Giang Hoang; Mohammed Hadi; Minh Ky Nguyen; Chitsan Lin; Ngoc Son Hai Nguyen; Ha Manh Bui; Huu-Tuan Tran; Thi Thu Huyen Dong (Regional Studies in Marine Science, 2026)

Stable yet hydrophilic graphene oxide nanomembranes by zwitterionic reduction for dye desalination - Sagnik Das; Ziwen Zhang; Erda Deng; Emmanuel M. Nsengiyumva; Ruveen Dias; Shixian Ha; Xiao Tong; Gbassey S.A. Oteme; Shweta Singh; Kai Chen; Prathima C. Nalam; Chang-Yong Nam; et al. (Chemical Engineering Journal, 2026)

A hybrid physics–Bayesian framework for fatigue design curves under cryogenic conditions with consideration of load ratio and residual stress - Yu Yao Lin; Yun-Jae Kim; Nak-Kyun Cho; Jin Ha Hwang; Kyu-Sik Park; Ali Mehmanparast; Do Kyun Kim (Ocean Engineering, 2026)

How effective are green roofs as building carbon sinks? Empirical evidence linking substrate, depth, and vegetation dynamics in the U.S. Great Plains - M.M. Lekhon Alam; Lee R. Skabelund; Charles W. Rice; James S. Lin; Jaeyoung Ha (Journal of Environmental Management, 2025)

Global Occurrence and Environmental Fate of Microplastics in Stormwater Runoff: Unlock the In-depth Knowledge on Nature-Based Removal Strategies - Van-Hiep Hoang; Minh-Ky Nguyen; Tuan-Dung Hoang; Hoang-Lam Nguyen; Chitsan Lin; Balal Yousaf; Minh Cuong Ha; Vu Khac Hoang Bui; Minh-Thuan Pham; S. Woong Chang; D. Duc Nguyen (Reviews of Environmental Contamination and Toxicology, 2025)

Engineering Critical Assessment of IMO Type C Tanks: A Comparative Study of Shell and Solid Element Models - Dong In Kim; Nak-Kyun Cho; Jin-Ha Hwang; Yu Yao Lin; Do Kyun Kim (Journal of Marine Science and Engineering, 2025)
In the present study, an Engineering Critical Assessment (ECA) is conducted for an International Maritime Organisation (IMO) Type C liquefied CO2 (LCO2) cargo tank to evaluate the effect of finite element configuration on structural integrity in the presence of potential flaws. With the increasing demand for LCO2 carriers to support carbon capture, utilisation, and storage (CCUS), conventional stress-based design approaches outlined in the International Gas Carrier (IGC) Code have limitations because they neglect imperfections resulting from fabrication and material. To assess these flaws, the fracture mechanics-based ECA methodology, as prescribed by the BS 7910 standard, is applied to a bilobe IMO type C tank designed for cryogenic and pressurised conditions. The assessment integrates fracture toughness, stress intensity factor, and applied loads. Both the two-dimensional shell element model and the three-dimensional solid element model are developed and compared in terms of stress distribution, safety factor for fracture, and fatigue crack growth predictions. Results show that while shell models offer computational efficiency, solid models capture bending stresses and stress concentrations at geometric discontinuities more accurately, resulting in higher reliability in ECA outcomes. The comparative analysis highlights that the web and butt weld near the centre bulkhead are the most vulnerable regions, and fatigue crack growth is highly sensitive to input data, such as stress intensity factor range and fatigue crack growth laws. These findings provide practical guidance for applying ECA in bilobe LCO2 tank design and safety assessment.

Effect of salinity on the physico-chemical characteristics of microalgal-bacterial granules treating shrimp farming wastewater - Mai-Duy-Thong Pham; Xuan-Thanh Bui; Thi-Kim-Quyen Vo; Nhu-Nguyet Phan; Thien-Tai Nguyen; Ky-Phuong-Ha Huynh; Chitsan Lin; Chettiyappan Visvanathan (Journal of Water Process Engineering, 2025)

Effect of honeycomb core cell geometry on the sandwich tube for internal blast loading - Vuong Nguyen-Van; Ngoc San Ha; H. Nguyen-Xuan; Xiaoshan Lin; Yi Min Xie; Guoxing Lu (Engineering Structures, 2025)

Hetero-atom-doped biochar as a sustainable catalyst for value-added upgrading of lignin derivatives: Optimizing dopant for enhancing conversion - Vo Thi Thanh Thuy; Hua-Chen Wu; Yu-chih Tsai; Ta Cong Khiem; Yi-Feng Lin; Ha Manh Bui; Yiu Fai Tsang; Kun-Yi Andrew Lin (Journal of Environmental Chemical Engineering, 2025)

Microplastic characteristics, transport, risks, and remediation in groundwater: a review - Van-Hiep Hoang; Minh-Ky Nguyen; Tuan-Dung Hoang; Nelson Rangel-Buitrago; Chitsan Lin; Minh-Thuan Pham; Minh Cuong Ha; Tan Phong Nguyen; Muhammad Shaaban; S. Woong Chang; D. Duc Nguyen (Environmental Chemistry Letters, 2025)

Novel Perspectives Focused on the Relationship Between Herpesvirus Encephalitis and Anti-GFAP-Antibody-Positive Astrocytopathy - Yuqiao Liao; Linxin Wen; Ruoyi Zheng; Yinan Shen; Teng-Ai Ha; Mingkai Lin; Ruogu Cheng; Ye Gao; Pei Shang (Molecular Neurobiology, 2025)

Impact of the root ratio of herbs and shrubs on the soil shear strength of collapsing walls in Benggang - Fang Shuai; Hua Wang; Fang Ha; Yuanyuan Zhan; Haoming Shen; Bo Ma; Yue Zhang; Jinshi Lin; Yanhe Huang; Fangshi Jiang (Journal of Mountain Science, 2025)

The effects of new satellite campuses on land prices——Evidence based on micro land transaction data in China - Wenjie Zhang; Lu Lin; Qiong Zhu; Dongyang Chen; Wei Ha (Applied Geography, 2025)

Microalgae − bacteria based wastewater treatment systems: Granulation, influence factors and pollutants removal - Mai-Duy-Thong Pham; Xuan-Thanh Bui; Thi-Kim-Quyen Vo; Thanh-Son Dao; Linh-Thy Le; Thi-Dieu-Hien Vo; Ky-Phuong-Ha Huynh; Thanh-Binh Nguyen; Chitsan Lin; Chettiyappan Visvanathan (Bioresource Technology, 2025)

LC–MS coupled with diagnostic ion strategy facilitated the discovery of 5-methylcoumarin meroterpenoids from Gerbera piloselloides - Shi-lin Chen; Ha Gao; Chen-xu Zhao; Tao Zhang; Zhong-mei Zou (Phytochemistry, 2025)

Selective precipitation of calcium phosphate, N-struvite, and K-struvite from raw seawater for resource recovery - Thi-Hanh Ha; Nicolaus N.N. Mahasti; Hiep-Quang Ha; Po-Lin Liao; Yao-Hui Huang; Ming-Chun Lu (Journal of Water Process Engineering, 2025)

Development and use of DJ-1 affinity microcolumns to screen and study small drug candidates for Parkinson's disease - Jacob C. Jones; Jiusheng Lin; Sadia Sharmeen; Md Masudur Rahman; Ha H. Truong; Ting-Rong Chern; Mark A. Wilson; David S. Hage (Analytica Chimica Acta, 2025)

Force mechanism analysis of composite microbial dust suppressants based on extracellular polymeric substances (EPS) mode components - Mei-Xuan Ha; Yu Liu; Yue Feng; Xiang-Ming Hu; Yan-Yun Zhao; Jin-Di Liu; Li Chen; Yan-Lin Qu (Journal of Environmental Management, 2024)

Retraction Note: Green supply chain, green leadership, consumer preferences, sustainability attitudes, and sustainable business advantage: a case of Vietnamese textile industry - Ka Yin Chau; Chen-Hsien Lin; Purevdulam Altantsetseg; Bushra Tufail; Thi Ha An Pham; Tran Thai Ha Nguyen (Environmental Science and Pollution Research, 2024)

Retraction Note: The moderating impact of government support on the relationship between tourism development and growth, natural resources depletion, sociocultural degradation, economic environment, and pollution reduction: case of Indonesian economy - Massoud Moslehpour; Afrizal Firman; Chen-Hsien Lin; İsmail Bilgiçli; Trung Kien Tran; Tran Thai Ha Nguyen (Environmental Science and Pollution Research, 2024)

Correction to: Neutralizing Antibody Sample Testing and Report Harmonization - Darshana Jani; Michele Gunsior; Robin Marsden; Kyra J. Cowan; Susan C. Irvin; Laura Schild Hay; Bethany Ward; Luke Armstrong; Mitra Azadeh; Liching Cao; Rebecca Carmean; Jason DelCarpini; et al. (The AAPS Journal, 2024)

Neutralizing Antibody Sample Testing and Report Harmonization - Darshana Jani; Michele Gunsior; Robin Marsden; Kyra J. Cowan; Susan C. Irvin; Laura Schild Hay; Bethany Ward; Luke Armstrong; Mitra Azadeh; Liching Cao; Rebecca Carmean; Jason DelCarpini; et al. (The AAPS Journal, 2024)
Immunogenicity testing and characterization is an important part of understanding the immune response to administration of a protein therapeutic. Neutralizing antibody (NAb) assays are used to characterize a positive anti-drug antibody (ADA) response. Harmonization of reporting of NAb assay performance and results enables efficient communication and expedient review by industry and health authorities. Herein, a cross-industry group of NAb assay experts have harmonized NAb assay reporting recommendations and provided a bioanalytical report (BAR) submission editable template developed to facilitate agency filings. This document addresses key bioanalytical reporting gaps and provides a report structure for documenting clinical NAb assay performance and results. This publication focuses on the content and presentation of the NAb sample analysis report including essential elements such as the method, critical reagents and equipment, data analysis, study samples, and results. The interpretation of immunogenicity data, including the evaluation of the impact of NAb on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract

Effective activation of peroxymonosulfate by CoCr-LDH for removing organic contaminants in water: from lab-scale to practical applications - Nguyen Trung Dung; Do Thi Hong Ha; Vu Dinh Thao; Nguyen Phuong Thao; Tran Dai Lam; Pham Thi Lan; Tran Thi Trang; Le Viet Ngan; Bui Dinh Nhi; Nguyen Thi Thuy; Kun-Yi Andrew Lin; Nguyen Nhat Huy (Environmental Science and Pollution Research, 2024)

What role financial development and resource-curse situation play in inclusive growth of Asian countries - Thi Ha An Pham; Chia-Yang Lin; Massoud Moslehpour; Thi Thuy Van Vo; Hai-Tuan Nguyen; Tran Thai Ha Nguyen (Resources Policy, 2024)

RETRACTED ARTICLE: Green supply chain, green leadership, consumer preferences, sustainability attitudes, and sustainable business advantage: a case of Vietnamese textile industry - Ka Yin Chau; Chen-Hsien Lin; Purevdulam Altantsetseg; Bushra Tufail; Thi Ha An Pham; Tran Thai Ha Nguyen (Environmental Science and Pollution Research, 2023)

Remediation of arsenic contaminated water and soil using mechanically (ball milling) activated and pyrite-amended electrolytic manganese slag - Zhihao Ha; Mengyu Ma; Xiaohan Tan; Yanxin Lan; Yanmin Lin; Tian C. Zhang; Dongyun Du (Environmental Research, 2023)

Supporting regional co-operation in the South China Sea with an initial assessment of the data-limited skipjack tuna fishery - Jeremy Prince; Xuefeng Wang; Kun Lin; Ani Suryanti; Sallehudin Jamon; Mudjekeewis D. Santos; Francisco SB. Torres; Nicko Amor L. Flores; Vu Viet Ha; Tran Thi Ngoc Anh (Marine Policy, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

Enhanced struvite (MgNH4PO4·6H2O) granulation and separation from synthetic wastewater using fluidized-bed crystallization (FBC) technology - Thi-Hanh Ha; Nicolaus N.N. Mahasti; Cai-Sheng Lin; Ming-Chun Lu; Yao-Hui Huang (Journal of Water Process Engineering, 2023)

RETRACTED ARTICLE: The moderating impact of government support on the relationship between tourism development and growth, natural resources depletion, sociocultural degradation, economic environment, and pollution reduction: case of Indonesian economy - Massoud Moslehpour; Afrizal Firman; Chen-Hsien Lin; İsmail Bilgiçli; Trung Kien Tran; Tran Thai Ha Nguyen (Environmental Science and Pollution Research, 2023)

Effect of biomass retention time on performance and fouling of a stirred membrane photobioreactor - Bao-Trong Dang; Xuan-Thanh Bui; Thanh-Tin Nguyen; Huu Hao Ngo; Long D. Nghiem; Ky-Phuong-Ha Huynh; Thi-Kim-Quyen Vo; Thi-Dieu-Hien Vo; Chitsan Lin; Shiao-Shing Chen (Science of The Total Environment, 2023)

MOF-templated hollow cobalt sulfide as an enhanced Oxone activator for degradation of UV Absorber: Key role of sulfur Vacancy-Induced highly active CoII sites - Ta Cong Khiem; Xiaoguang Duan; Wei-Jie Liu; Young-Kwon Park; Ha Manh Bui; Wen-Da Oh; Suresh Ghotekar; Yiu Fai Tsang; Kun-Yi Andrew Lin (Chemical Engineering Journal, 2023)

Anti-drug Antibody Sample Testing and Reporting Harmonization - Darshana Jani; Robin Marsden; Michele Gunsior; Laura Schild Hay; Bethany Ward; Kyra J. Cowan; Mitra Azadeh; Breann Barker; Liching Cao; Kristin R. Closson; Kelly Coble; Sanjay L. Dholakiya; et al. (The AAPS Journal, 2022)
A clear scientific and operational need exists for harmonized bioanalytical immunogenicity study reporting to facilitate communication of immunogenicity findings and expedient review by industry and health authorities. To address these key bioanalytical reporting gaps and provide a report structure for documenting immunogenicity results, this cross-industry group was formed to establish harmonized recommendations and a develop a submission template to facilitate agency filings. Provided here are recommendations for reporting clinical anti-drug antibody (ADA) assay results using ligand-binding assay technologies. This publication describes the essential bioanalytical report (BAR) elements such as the method, critical reagents and equipment, study samples, results, and data analysis, and provides a template for a suggested structure for the ADA BAR. This publication focuses on the content and presentation of the bioanalytical ADA sample analysis report. The interpretation of immunogenicity data, including the evaluation of the impact of ADA on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract

A multi-step nitrifying microbial enrichment to remove ammonia and nitrite in brackish aquaculture systems - Dao Thi Anh Tuyet; Le Minh Hiep; Ha Thi Binh; Le Thanh Huyen; Sen-Lin Tang; Pei-Wen Chiang; Do Manh Hao (Biodegradation, 2022)

Histone deacetylase 6-mediated downregulation of TMEM100 expedites the development and progression of non-small cell lung cancer - Yanyun Wang; Minwen Ha; Man Li; Lin Zhang; Yitong Chen (Human Cell, 2022)

Contamination, source attribution, and potential health risks of heavy metals in street dust of a metropolitan area in Southern Vietnam - Nguyen Duy Dat; Van-Truc Nguyen; Thi-Dieu-Hien Vo; Xuan-Thanh Bui; Manh-Ha Bui; Ly Sy Phu Nguyen; Xuan-Cuong Nguyen; Anh Thi-Kim Tran; Thi-Tinh-Au Nguyen; Yun-Ru Ju; Thi-Minh-Trang Huynh; Duy-Hieu Nguyen; et al. (Environmental Science and Pollution Research, 2021)

In vitro study on α-amylase and α-glucosidase inhibitory activities of a new stigmastane-type steroid saponin from the leaves of Vernonia amygdalina - Hoang Le Tuan Anh; Le Ba Vinh; Le Thi Lien; Pham Viet Cuong; Masayoshi Arai; Tran Phuong Ha; Hoang Ngoc Lin; Ton That Huu Dat; Le Canh Viet Cuong; Young Ho Kim (Natural Product Research, 2021)

Regional eco-efficiency evaluation and spatial pattern analysis of the Yangtze River Economic Zone - Lin Ha; Jianjun Tu; Jianping Yang; Chunhai Xu; Jiaxing Pang; Debin Lu; Zuolin Yao; Wenyu Zhao (Journal of Geographical Sciences, 2020)

Recent geodetic mass balance and extent changes of very small glaciers in the Hulugou Basin, Central Qilian Mountains, China - Chunhai Xu; Zhongqin Li; Feiteng Wang; Lin Ha; Yousif Elnour Yagoub; Shuang Jin (Journal of Earth System Science, 2019)

NADP+-dependent cytosolic isocitrate dehydrogenase provides NADPH in the presence of cadmium due to the moderate chelating effect of glutathione - Hyo Je Cho; Ha Yeon Cho; Jeen-Woo Park; Oh-Shin Kwon; Hyun-Shik Lee; Tae Lin Huh; Beom Sik Kang (JBIC Journal of Biological Inorganic Chemistry, 2018)

Evidence that NF-κB and MAPK Signaling Promotes NLRP Inflammasome Activation in Neurons Following Ischemic Stroke - David Yang-Wei Fann; Yun-An Lim; Yi-Lin Cheng; Ker-Zhing Lok; Prasad Chunduri; Sang-Ha Baik; Grant R. Drummond; S. Thameem Dheen; Christopher G. Sobey; Dong-Gyu Jo; Christopher Li-Hsian Chen; Thiruma V. Arumugam (Molecular Neurobiology, 2018)

Effects of sand burial on the survival and growth of two shrubs dominant in different habitats of northern China - Hao Qu; Ha-Lin Zhao; Xue-Yong Zhao; Xiao-An Zuo; Shao-Kun Wang; Min Chen (Environmental Monitoring and Assessment, 2017)

Interdecadal change in the Northern Hemisphere seasonal climate prediction skill: part II. predictability and prediction skill - XiaoJing Jia; June-Yi Lee; Hai Lin; Harry Hendon; Kyung-Ja Ha (Climate Dynamics, 2014)

Interdecadal change in the Northern Hemisphere seasonal climate prediction skill: part I. The leading forced mode of atmospheric circulation - XiaoJing Jia; June-Yi Lee; Hai Lin; Andrea Alessandri; Kyung-Ja Ha (Climate Dynamics, 2014)

The role of serine 190 in FOXO nuclear export and cell death induction in Drosophila melanogaster - Yoon Ki Hong; Dahye Lee; Soojin Hwang; Se Min Bang; Haemin Jeong; Seoyun Choi; Tan-Viet Phamd; Lin-Woo Kang; Young-Ha Lee; Kyoung Sang Cho; Guang-Ho Cha (Genes & Genomics, 2014)

A prospective clinical study in hepatitis B e antigen-negative chronic hepatitis B patients with stringent cessation criteria for adefovir - Minghao Ha; Guotong Zhang; Shu Diao; Mingfang Lin; Liping Sun; Huiyuan She; Chenbao Kuan; Lihui Shen; Chunhong Huang; Wenjuan Shen; Zhongming Huang (Archives of Virology, 2012)

QTL identification of flowering time at three different latitudes reveals homeologous genomic regions that control flowering in soybean - Weixian Liu; Moon Young Kim; Yang Jae Kang; Kyujung Van; Yeong-Ho Lee; Peerasak Srinives; Dong Lin Yuan; Suk-Ha Lee (Theoretical and Applied Genetics, 2011)

Linking root morphology, longevity and function to root branch order: a case study in three shrubs - Gang Huang; Xue-yong Zhao; Ha-lin Zhao; Ying-xin Huang; Xiao-an Zuo (Plant and Soil, 2010)

Vertical distribution, biomass, production and turnover of fine roots along a topographical gradient in a sandy shrubland - Gang Huang; Xue-yong Zhao; Yan-gui Su; Ha-lin Zhao; Tong-hui Zhang (Plant and Soil, 2008)